2016
DOI: 10.1007/s10856-016-5802-6
|View full text |Cite
|
Sign up to set email alerts
|

In vitro comparison of the efficacy of TGF-β1 and PDGF-BB in combination with freeze-dried bone allografts for induction of osteogenic differentiation in MG-63 osteoblast-like cells

Abstract: Predictable regeneration of alveolar bone defects has always been a challenge in implant dentistry. Bone allografts are widely used bone substitutes with controversial osteoinductive activity. This in vitro study aimed to assess the osteogenic potential of some commercially available freeze-dried bone allografts supplemented with human recombinant platelet-derived growth factor-BB and transforming growth factor beta-1. Cell viability, mineralization, and osteogenic gene expression of MG-63 osteoblast-like cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…For a comprehensive overview on the signalling pathways through which PDGF-BB elicits downstream cascades, refer to previous reviews on the topic (Andrae et al, 2008;Heldin and Westermark, 1999;Tallquist and Kazlauskas, 2004). PDGFR can also interact with integrins, through the Na + /H + exchanger regulatory factors (NHERFs) that link it to focal adhesion kinase and cytoskeleton (James et al, 2004;Veevers-Lowe et al, 2011). In turn, PDGFRs can be also affected by the ECM components (DeMali et al, 1999;Veevers-Lowe et al, 2011).…”
Section: Pdgf-bb Is Predominantly Expressed During Tendon Healingmentioning
confidence: 99%
See 2 more Smart Citations
“…For a comprehensive overview on the signalling pathways through which PDGF-BB elicits downstream cascades, refer to previous reviews on the topic (Andrae et al, 2008;Heldin and Westermark, 1999;Tallquist and Kazlauskas, 2004). PDGFR can also interact with integrins, through the Na + /H + exchanger regulatory factors (NHERFs) that link it to focal adhesion kinase and cytoskeleton (James et al, 2004;Veevers-Lowe et al, 2011). In turn, PDGFRs can be also affected by the ECM components (DeMali et al, 1999;Veevers-Lowe et al, 2011).…”
Section: Pdgf-bb Is Predominantly Expressed During Tendon Healingmentioning
confidence: 99%
“…PDGFR can also interact with integrins, through the Na + /H + exchanger regulatory factors (NHERFs) that link it to focal adhesion kinase and cytoskeleton (James et al, 2004;Veevers-Lowe et al, 2011). In turn, PDGFRs can be also affected by the ECM components (DeMali et al, 1999;Veevers-Lowe et al, 2011).…”
Section: Pdgf-bb Is Predominantly Expressed During Tendon Healingmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, we showed that PRP accelerated bone union and induced a reduction of the bone union period in both rats and humans with spinal posterolateral fusion (PLF) [8][9][10]. It appears that platelet-derived growth factor (PDGF) plays an essential role in such effects as it has the ability to promote bone fusion [11]. PDGF is a member of a large family of GFs secreted by human vascular endothelial cells and fibroblasts to induce phosphorylation and activation of the PDGF receptor (PDGFR), which thereby activates downstream pathways that regulate cell growth and division.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of segmental bone defects caused by trauma, infection, or bone tumor resection remains a great challenge for orthopedic surgeons, and the growing clinical demands for bone substitutes highlights the need for researchers to both develop new bone scaffolds and improve the process of bone regeneration 1 . The latter has been the focus of many studies and several tissue-engineering techniques have been proposed to enhance osteogenesis inside bone scaffolds 2 , such as pre-seeding scaffolds with mesenchymal stem cells 3 , delivering growth factors like bone morphogenetic protein 2 (BMP-2) or transforming growth factor β1 (TGFβ-1) within scaffolds 4 - 5 , or pre-vascularization of scaffolds in vitro before implantation 6 . While each of these methods have been successful to some extent they all have disadvantages, including extended preparation time and a high cost for the final product.…”
Section: Introductionmentioning
confidence: 99%